Numerical model of a composite airfoil segment with piezoelectric sensors - Bartošek, Jan (Materiali in tehnologije, 2014)
A numerical model of an airfoil segment with piezoelectric sensors was created with commercial finite-element software Abaqus and its response to impact loading was compared with experimental results. The wing segment was made of woven-glass/epoxy composite with a varying number of plies and different types of weave. The material properties were experimentally determined from the tensile tests and used in the finite-element model of a rectangular plate. The results of the experimental modal analysis of a composite rectangular plate made of the same material as the segment were compared to the results of the numerical analysis and the parameters of the numerical model were adjusted. Finally, a numerical model of the whole segment was created and validated on the basis of the results of the corresponding experimental modal analysis. Moreover, piezoelectric sensors were glued to the segment and their response to dynamic loading was compared to the results of the numerical simulation.
Keywords: composite; steklena vlakna; epoksi smola; piezoelectricity; finite-element analysis; kompozitna tkanina; piezoelektrika; modal analysis; končni elementi; modalna analiza